Ethnological-Historiographic View on Seven Ancient Extant Christian Liturgies - Primorac, Jaksa (Collectanea Christiana orientalia, 2024)
The author analyses comparatively seven ancient extant Christian liturgies: Roman Catholic Tridentine mass, Byzantine liturgy of the Eastern Orthodox Churches, four liturgies of the Oriental Orthodox Churches: Alexandrian-Coptic, Antiochian-Syriac, Armenian and Ethiopian, and finally the liturgy of the Churches of the East: Assyrian and Ancient. Furthermore, the author researches inculturation of Antiochian-Syriac liturgy and Churches of the East liturgy in South India, as well as liturgies in Eastern Catholicism and Western Orthodoxy. This study explores historical events that are crucial to understanding the origin and development of ancient liturgies, as well as major architecture, painting, drama and music aspects of liturgies from ethnological perspective.